VD_FINDINFO HC / 2014 / 1016 vom 8. Dezember 2014 - VD Tribunal cantonal (2014)
DIVORCE, AUTORITÉ PARENTALE, RELATIONS PERSONNELLES, ENFANT, INTÉRÊT DE L'ENFANT, CURATELLE | 133 al. 3 CC, 133 CC, 308 al. 2 CC, 308 CC, 92 CPC